America Inc.? : Innovation and Enterprise in the National Security State - Weiss, Linda (Linda M.) (Book collections on Project MUSE., 2014)
"For more than half a century, the United States has led the world in developing major technologies that drive the modern economy and underpin its prosperity. Linda Weiss attributes the U.S. capacity for transformative innovation to the strength of its national security state, a complex of agencies, programs, and hybrid arrangements that has developed around the institution of permanent defense preparedness and the pursuit of technological supremacy. In America Inc.? she examines how that complex emerged and how it has evolved in response to changing geopolitical threats and domestic political constraints, from the Cold War period to the post-9/11 era."--Back cover